Comparative floristic composition and diversity indices in two Algerian steppe regions (Djelfa and Tiaret) - Doukani, Radjaa; GRANDI , Mohamed; CHEHMA , Abdelmadjid; SARMOUM , Mohamed (Ecological Questions, 2026)
Understanding floristic patterns in Algerian steppe ecosystems is essential for assessing the extent of ongoing ecological degradation. This study provides a comparative floristic analysis of two major steppe regions, Djelfa and Tiaret, based on field surveys conducted during spring campaigns from 2022 to 2024 at 56 sampling stations. A total of 134 taxa belonging to 32 families were identified. Asteraceae (26.9%), Poaceae (10.5%) and Fabaceae (6.7%) form the dominant assemblage, while the biological spectrum is predominantly therophytic (40%), reflecting strong adaptation to arid conditions and increasing ecosystem disturbance. Chorological analysis reveals a dual Mediterranean (32.1%) and Saharan (29.1%) influence, consistent with the biogeographical position of the two regions. Diversity indices show significant structural contrasts: Tiaret exhibits higher and more balanced diversity (H’ = 4.51; E = 0.97; 1/D = 80.9), while Djelfa displays reduced floristic stability (H’ = 4.39; E = 0.95; 1/D = 66.2) and greater fragmentation. Overall, the results reveal structural indicators of ecological imbalance in Djelfa, suggesting a higher degree of anthropogenic pressure, and underscore the need for ecological restoration and sustainable rangeland management to preserve the biodiversity and functional integrity of Algerian steppe landscapes.